Presidential elections: strategies of American electoral politics - Polsby, Nelson W.; Wildavsky, Aaron (New Delhi, 1976)
The central purpose of this book is to provide what for want of a better name might be called civic education. Our notion is that people are entitled to information about the choices they make-not merely the alternatives presented, but also the processes that produce alternatives. Since, in the United States, presidential elections entail significant choices for millions of Americans and in one way or another affect nearly everyone else, it has seemed to us worthwhile to offer a discussion of the entire presidential election process that is unsentimental, nonpartisan, and explicit about how and why things happen as they do. Ideally, this should help people follow, and participate in, events in ways that make sense to them, minimize the production of false hopes, and supply an antidote to the unrealistic and cynical views of politics that tend to develop when people do not understand why things turn out contrary to their fondest desires.
Keywords: Elections - U.S.A